Enhancing Student Confidence in Diabetes Management Skills Through Pharmacist-Run Group Classes in a Community Library - Regina Ginzburg; Christine Chim (University of Minnesota Libraries Publishing, 2022)
Purpose: To evaluate student pharmacists' confidence after providing education within diabetes groups in a non-medical community setting. Program Description: Three 8-week diabetes group courses were developed and executed within a local public library. The courses aimed to teach participants with diabetes how to effectively manage their medical condition to prevent future related complications. Student pharmacists were responsible for checking and recording the patients' vitals, assisting in answering questions posed by the participants throughout the session, presenting different medication information each week, and creating a brochure which described the highlights of the specific week's medication class. The student pharmacists were then surveyed regarding their confidence level in providing diabetes education in the future as well as their experience of working within these groups. Summary: Seventeen student pharmacists participated in three 8-week sessions. The majority of the student pharmacists reported increased confidence in being able to provide diabetes education as well as newfound empathy for persons with diabetes on how to manage their medical condition.